Acute Conditioning of Antigen-Expanded CD8+ T Cells via the GSK3β-mTORC Axis Differentially Dictates Their Immediate and Distal Responses after Antigen Rechallenge - Taborska, Pavla; Stakheev, Dmitry; Svobodova, Hana; Strizova, Zuzana; Bartunkova, Jirina; Smrz, Daniel (Cancers, 2020)
CD8+ T cells protect against tumors and intracellular pathogens. The inflammatory cytokines IL-2, IL-15, and IL-7 are necessary for their expansion. However, elevated serum levels of these cytokines are often associated with cancer, poorer prognosis of cancer patients, and exhaustion of antigen-expanded CD8+ T cells. The impact of acute conditioning of antigen-expanded CD8+ T cells with these cytokines is unknown. Here, we generated antigen-expanded CD8+ T cells using dendritic cells and PC-3 cells. The cells were acutely (18-24 h) conditioned with IL-2 and either the GSK3β inhibitor TWS119, the mTORC1 inhibitor rapamycin, or the mTORC1/2 inhibitor Torin1, then their immediate and post-re-expansion (distal) cytokine responses after antigen rechallenge were evaluated. We found that acute IL-2 conditioning upregulated the immediate antigen-induced cytokine response of the tested cells. Following their re-expansion, however, the cells showed a decreased cytokine response. These IL-2 conditioning-mediated impacts were counteracted with TWS119 or rapamycin but not with Torin1. Our data revealed that the acute conditioning of antigen-expanded CD8+ T cells with IL-2 modulates the GSK3β-mTORC signaling axis. This modulation differentially affected the immediate and distal cytokine responses of the cells. The acute targeting of this signaling axis could, therefore, represent a novel strategy for the modulation of antigen-expanded CD8+ T cells.
Keywords: CD8+ T cells; antigen rechallenge; rapamycin; mTOR; cytokine starvation; Torin1; GSK-3β; TWS119; Tim-3